ANALISIS PENERIMAAN APLIKASI SISKEUDES Di LINGKUNGAN PEMERINTAH DAERAH KABUPATEN SAMBAS - Eko Febri Lusiono; Suharman Suharman (Politeknik Negeri Batam, 2017)
The Research of SISKEUDES Application Acceptance Analysis in local government environment of Sambas district is to know the extent of acceptance of SISKUEDES application in Sambas district. Total respondents were 50 village apparatus from ten districts in Sambas district. The sub-districts are Selakau, Selakau Timur, Salatiga, Pemangkat, Semparuk, Tebas, Sebawi, Sambas, Sejangkung, Sajad and Subah sub-districts. The study was conducted using Theory Acceptance Model (TAM) with seven pure constructs (seven hypotheses). Actual Use (AU) as the dependent variable, while perceived ease of use (PEOU), perceived usefulness (PU), attitude (ATT), behavioral intention (BI) as independent variables. Based on multiple regresilinear regression analysis with SPSS 17 application it can be seen that H1, H2, H3, and H5 are accepted because the significance value in Anova table is smaller than 0.05. While H4, H6, and H7 rejected. Based on this it can be concluded that perceived usefulness perceptions and perceived ease of use perceptions become the benchmark of rural apparatus to accept an application.